2008
DOI: 10.1680/macr.2008.60.6.441
|View full text |Cite
|
Sign up to set email alerts
|

Code modelling of reinforced-concrete deep beams

Abstract: Code provisions for shear design of deep beams have commonly developed from limited test results. There are also very few studies on the validity of shear-carrying capacities of concrete and shear reinforcement in code provisions including strut-and-tie models. The present study investigates the effect of different parameters on the shearcarrying capacities of concrete and shear reinforcement in four code provisions: ACI 318-99 and CIRIA Guide 2 for empirical formulae, and ACI 318-05 and Eurocode (EC) 2 for st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…In general, longitudinal reinforcement keeps within the elastic state when the structural failure of deep beams are governed by compressive crushing of concrete struts. 19 In addition, many investigations 2,11,16 showed that vertical and horizontal shear reinforcements do not commonly reach the yield strength when shear span-to-overall depth ratio is less than approximately 1.0 and more than 1.0, respectively. …”
Section: Basic Assumptionmentioning
confidence: 99%
See 3 more Smart Citations
“…In general, longitudinal reinforcement keeps within the elastic state when the structural failure of deep beams are governed by compressive crushing of concrete struts. 19 In addition, many investigations 2,11,16 showed that vertical and horizontal shear reinforcements do not commonly reach the yield strength when shear span-to-overall depth ratio is less than approximately 1.0 and more than 1.0, respectively. …”
Section: Basic Assumptionmentioning
confidence: 99%
“…2 As the height of the top nodal zone is assumed to be 0.8 t w from the concrete effective stresses in the nodal zones, the distance between top and bottom nodes is calculated from the following equation:…”
Section: Geometrical Dimension Of Concrete Strutsmentioning
confidence: 99%
See 2 more Smart Citations
“…Artificial neural networks (ANN)were previously used to predicting the concrete properties (Flood et al, 2001;Pannir selvam et al, 2008;Perera et al, 2010;Yang et al, 2008;Guang and Zong, 2000;Goh ATC, 1995;Sanad and Saka, 2001;Jamal et al, 2007;Arslan, 2009;Arslan et al, 2007).From a literature study it could be find that there is no investigation on the combined effects of fibers and nano-silica on the mechanical Properties of SCC using ANN.…”
Section: Introductionmentioning
confidence: 99%